Magnetic Graphene Oxide Conjugated with Polyamidoamine Dendrimer (MGO-PAMAM) as Heavy Metal Adsorbent: Bibliometric Analysis using Google Scholar Indexed VOSViewer - Brigitta Stacia Maharani; Asep Bayu Dani Nandiyanto (Indonesian Society of Limnology, 2022)
This study aims to analyses the scope of research related to magnetic graphene oxide conjugated with polyamidoamine dendrimer (MGO-PAMAM) material as an adsorbent for heavy metals using bibliometric evaluation and data mapping with VOSViewer software. MGO-PAMAM material research data was collected from the Google Scholar database with criteria in the form of MGO journals and keywords, dendrimers, polyamidoamine, PAMAM, synthesis, and adsorption in 2018–2023. Based on the search results, 175 relevant journal articles were found. The number of articles has fluctuated from 2018 to 2023. This is due to the COVID-19 pandemic that is happening globally. This study can provide information on the pattern of distribution of journal articles and the quality of research developments related to polyamidoamine dendrimer material as an adsorbent for heavy metals in the last 5 years. This bibliometric analysis is expected to help researchers recognize research trends related to polyamidoamine dendrimer materials as heavy metal adsorbents globally and recommend future research prospects.